2019
DOI: 10.7197/223.vi.568582
|View full text |Cite
|
Sign up to set email alerts
|

A short review on the comparison of consultation systems and tools in the emergency department practice: Tele-consultation

Abstract: Emergency department (ED) consultation is an important part of acute patient care and one of the major determinants of ED length of stay (LOS). ED consultations between physicians who may not be in the same location frequently, require a tool to reach out one another and communicate. This paper reviews the historical change and development of consultation tools. The literature on ED consultation methods have been accumulating for the last two decades as the diversity of these methods has increased with technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…These ndings are consistent with the fact that cerebrovascular diseases are the most common reason for neurologic consultation. This is similar to another study by Sevilay Vural and her colleagues which also showed motor de cit, speech disorder, conscious impairment, facial asymmetry, and sensory system dysfunction were the major neurologic examination ndings in those subjects [14] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These ndings are consistent with the fact that cerebrovascular diseases are the most common reason for neurologic consultation. This is similar to another study by Sevilay Vural and her colleagues which also showed motor de cit, speech disorder, conscious impairment, facial asymmetry, and sensory system dysfunction were the major neurologic examination ndings in those subjects [14] .…”
Section: Discussionsupporting
confidence: 91%
“…In another study conducted in Cameron, Malaria and other related central nervous system infections, which are endemic to sub-Saharan African countries, were the most common non-traumatic neurological causes in the ER [13] . Nevertheless, CNS infections account for a smaller number of patients in emergency admissions in developed countries [14] . Although Somalia is a sub-Saharan African nation, CNS infections were only 0.6% of the cases in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This platform is considered to be a useful application to coordinate intradepartmental communication [9]. Moreover, WhatsApp is used by ED physicians and consulting physicians to exchange medical information during ED consultations [10,11].…”
Section: Introductionmentioning
confidence: 99%